Toll-like receptors and their soluble forms differ in the knee and thumb basal osteoarthritic joints - Goncalo Barreto; Jerker Sandelin; Abdelhakim Salem; Dan C Nordström; Eero Waris (Acta Orthopaedica, 2017)
Background and purpose — Although the pathogenesis of osteoarthritis (OA) is not well understood, chondrocyte-mediated inflammatory responses (triggered by the activation of innate immune receptors by damage-associated molecules) are thought to be involved. We examined the relationship between Toll-like receptors (TLRs) and OA in cartilage from 2 joints differing in size and mechanical loading: the first carpometacarpal (CMC-I) and the knee. Patients and methods — Samples of human cartilage obtained from OA CMC-I and knee joints were immunostained for TLRs (1–9) and analyzed using histomorphometry and principal component analysis (PCA). mRNA expression levels were analyzed with RT-PCR. Collected synovial fluid (SF) samples were screened for the presence of soluble forms of TLR2 and TLR4 by enzyme-linked immunosorbent assay (ELISA). Results — In contrast to knee OA, TLR expression in CMC-I OA did not show grade-dependent overall profile changes, but PCA revealed that TLR expression profiles clustered according to their cellular compartment organization. Protein levels of TLR4 were substantially higher in knee OA than in CMC-I OA, while the opposite was the case at the mRNA level. ELISA assays confirmed the presence of soluble forms of TLR2 and TLR4 in SF, with sTLR4 being considerably higher in CMC-I OA than in knee OA. Interpretation — We observed that TLRs are differentially expressed in OA cartilage, depending on the joint. Soluble forms of TLR2 and TLR4 were detected for the first time in SF of osteoarthritic joints, with soluble TLR4 being differentially expressed. Together, our results suggest that negative regulatory mechanisms of innate immunity may be involved in the pathomolecular mechanisms of osteoarthritis.